Analisis Faktor-Faktor yang Mempengaruhi Penjualan terhadap Perolehan Laba di PT Hino Finance Indonesia pada Tahun 2023 - Sutarsa, Monika; Primadani Firmansyah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to analyze the factors that influence sales towards profit acquisition at PT Hino Finance Indonesia in 2023, which recorded a significant increase in profit. The method used in this study is a descriptive qualitative approach, with data collection through literature studies that include books, journals, notes, and reports that are relevant to the topic being studied. Documentation techniques are also applied to collect, store, and manage related documents. The results of this study indicate that there are several factors that influence sales, such as product quality, product price, and marketing strategies implemented by the company. Improving product quality and adjusting competitive prices play an important role in attracting consumer interest and increasing sales. In addition, external factors such as economic conditions and market competition also influence purchasing decisions and ultimately contribute to increasing company profits. This study provides deeper insight into the factors that influence profit achievement at PT Hino Finance Indonesia and can be a reference for other companies in formulating more effective sales strategies.